SISTEM INFORMASI ARUS KAS STUDI KASUS PADA PT ADHINATA KARYA MARMER - Wasiyanti, Sri (www.bsi.ac.id, 2015)
ABSTRACT Cash is an important component in the sustainability of a company. Through cash, funds flowing in into the organization's resources and flows out as a cost. The flow of incoming funds are often not proportional to the flow of funds out. It is therefore necessary cash flow management processes into a job that should have gained serious attention in the financial management in a company. Unfortunately, cash flow management, or better known as Cash Flow Management, often regarded as one of the main aspects of some of the issues faced by organizations in implementing the company's operations. Problems faced by organizations due to poor cash flow management often arises in many cases from the simple to the complex situation. This is because not all companies understand the management of cash flow. For example, when the cash is received (cash inflow) and cash paid (cash outflow) occurs is not planned, the organization might encounter problems delay the payment of staff salaries, delays in the implementation of the program, and the outstanding balance which increasingly growing. Based on the problems above, this research will discuss the system of cash flows associated with cash transactions, both Cash In and Cash Out. The report formed the transaction is Cash Flow and Cash Out Login using research methods, which are used as a research location is PT. Adhinata Marble Works. The expected outcome of this research is to produce a cash flow-based handling of computerized so as to speed up the transaction process until the presentation of cash flow statements on time.Keywords:Information system, cash flow